2019
DOI: 10.1029/2019wr024941
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Disconnection of Groundwater From Managed‐Ephemeral Surface Water During Drought and Conjunctive Agricultural Use

Abstract: The physics of disconnection between interrelated surface and groundwater has evolved considerably in recent years, especially since conjunctive use of water resources is increasingly dependent on groundwater resilience, but methods to measure disconnection on a river basin scale are lacking especially for managed‐ephemeral and irrigated‐agricultural systems. Multiyear drought limited surface water along Rincon Valley within the Elephant Butte Irrigation District (EBID) in the arid, Lower Rio Grande Basin of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…For example, it could be stated that “the fact that a model cannot correctly predict groundwater dynamics does not mean that it cannot be used to predict streamflow,” and the only way to decide this is to consider auxiliary evidence of groundwater‐surface water interaction. Consider the following three possibilities: The streamflow and groundwater systems were “connected” both prior to and during the drought; The streamflow and groundwater systems were connected predrought, but became “disconnected” during the drought (see also Fuchs et al, ; Kinal & Stoneman, ); and The streamflow and groundwater systems were not connected predrought, nor during the drought. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it could be stated that “the fact that a model cannot correctly predict groundwater dynamics does not mean that it cannot be used to predict streamflow,” and the only way to decide this is to consider auxiliary evidence of groundwater‐surface water interaction. Consider the following three possibilities: The streamflow and groundwater systems were “connected” both prior to and during the drought; The streamflow and groundwater systems were connected predrought, but became “disconnected” during the drought (see also Fuchs et al, ; Kinal & Stoneman, ); and The streamflow and groundwater systems were not connected predrought, nor during the drought. …”
Section: Discussionmentioning
confidence: 99%
“…The streamflow and groundwater systems were "connected" both prior to and during the drought; 2. The streamflow and groundwater systems were connected predrought, but became "disconnected" during the drought (see also Fuchs et al, 2019;Kinal & Stoneman, 2012); and 3. The streamflow and groundwater systems were not connected predrought, nor during the drought.…”
Section: Groundwater-surface Water Connectionsmentioning
confidence: 99%
“…Limited regional coherence indicates a larger role of local physiographic and land cover/use characteristics in influencing drying characteristics than previously expected. Prior work has found numerous local characteristics influencing stream intermittency, including watershed storage (McDonnell et al., 2018; Nippgen et al., 2016; Tashie et al., 2020), subsurface heterogeneity (Herzog et al., 2019; Klaus & Jackson, 2018; Zimmer & McGlynn, 2017), land use change (Julian et al., 2015), and water withdrawals (Fuchs et al., 2019; Perkin et al., 2017). Potential drivers are explored in Section 3.3.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, groundwater hydrochemistry could be controlled by the coupling of multiple mechanisms, including evaporation-condensation, leaching and dissolution, precipitation, flushing and mixing, ion exchange, and subsurface biological activity [22,26,31,32]. Additionally, researchers found that spatiotemporal patterns of ion contents in groundwater can provide an insight into the salt origin, evolution, and migration pathways within the aquifers [26,33], which is helpful to understand groundwater water-salt migration in arid areas [34,35]. Yet, alteration of groundwater water-salt circulation by land use change and its influence on groundwater hydrochemistry evolution in the long term are not well known in the oasis-desert region of the Tarim Basin, particularly under the impact of cultivated area expansion.…”
Section: Introductionmentioning
confidence: 99%